Islam Throughout the Diaspora: Balancing Cultural Characteristics, Religious Beliefs, and Criminal Activity (the Case of Italy) - Fronzoni, Vasco (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
The purpose of this study is to revitalizes the debate around the plural structure of Western societies and what cultural traits and religious dimensions mean. Starting from some news reported by the Italian media often with misleading headlines, the article analyze the processes of inclusion of Islam in European legal systems, with a particular focus on the relationship between the religious factor and the criminal sphere. Cyclically the Italian media, in reporting some news stories, associate crimes with the religious affiliation of their perpetrators, polarizing attention on Islam rather than on the criminal. The research method used is qualitative, based on media and library research, with a jurisprudence analysis and a legal approach as an analytical tool to investigate the stated problems. Although in Italy the relationship between the religious factor and criminal law certainly shows a concrete and tangible interest, despite the lack of a dedicated constitutional model as well as a current and specific law on religious freedom. However, doctrinal discussions do not always correctly emphasize the difference between behaviors guided by cultural heritages and those imposed by religious beliefs. The results of this study indicate that, if on the one hand there is a tangible religious illiteracy, internal and external to the Muslim communities living in the diaspora, on the other hand the cultural sphere must be distinguished from the religious one, and a hermeneutic paradigm exercised by suitable and accredited subjects is needed. In fact, the appropriate hermeneutic coordinates are needed both on the legal and on the religious level to live Islam correctly as migrants residing in the diaspora or as Muslims with citizenship. In conclusion, the topic is essential, due to the gap in the research, which often confuses the cultural level with the religious one, and the aim is to clarify the point and provide a new paradigm.In this way discrimination is avoided and Italian judges and legislators will be able to have a more informed and therefore more sensitive approach towards religious minorities in Italy.